2019
DOI: 10.3776/tpre.2019.v9n2p47-64
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Mindsets: The Hassles and Hopes of Co-teaching in Teacher Preparation

Abstract: Isolation between academic fields is an unfortunate reality in higher education and teacher education. Whereas current educational reforms invoke a need to collaborate, faculty are often unsure of how to design collaborative experiences. Research argues for the use of co-teaching to engage teacher candidates in beneficial learning experiences where instructors model the collaborative practices desired in those candidates. Additionally, the use of co-teaching in rural settings is shown to address some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Whether instructors provide joint feedback on an assignment or informal feedback in class, different voices built in as supports allow pre-service teachers to grow professionally (Burns & Mintzberg, 2019). Guidry and Howard (2019) discussed the potential impact of co-teaching on both student-teacher relationships and student relationships to content. Further, Wehunt and Weatherford (2014) found that co-teaching in higher education helps students and instructors develop mutual respect, leading to increased engagement.…”
Section: Benefits Of Co-teaching In Teacher Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether instructors provide joint feedback on an assignment or informal feedback in class, different voices built in as supports allow pre-service teachers to grow professionally (Burns & Mintzberg, 2019). Guidry and Howard (2019) discussed the potential impact of co-teaching on both student-teacher relationships and student relationships to content. Further, Wehunt and Weatherford (2014) found that co-teaching in higher education helps students and instructors develop mutual respect, leading to increased engagement.…”
Section: Benefits Of Co-teaching In Teacher Preparationmentioning
confidence: 99%
“…Wilson and Ferguson (2017) advocated that having two experts to engage with allows students to feel more comfortable asking hard questions and taking risks. Additionally, connections between concepts can be made explicit, and information can be presented in multiple ways, leading to lasting retention and skill-building (Guidry & Howard, 2019). Various studies show that presenting material in multiple ways is beneficial from the instructors' perspective (Morelock et al, 2017;Wehunt & Weatherford, 2014).…”
Section: Benefits Of Co-teaching In Teacher Preparationmentioning
confidence: 99%
See 2 more Smart Citations